Peningkatan Hasil Belajar Seni Tari Melalui Media Audio Visual - Warsilah Warsilah (Universitas Mathla'ul Anwar Banten, 2021)
This study aims to determine whether there is an increase in learning outcomes of the dance material of the Giring-giring dance from Kalimantan through Audio Visual media for grade VIII C students of SMP Negeri 1 Cibadak. This study applies audio-visual media in learning the art of giring dance material from Kalimantan and is carried out in two cycles. Each cycle consists of four stages, namely, planning, action, observation, and reflection and evaluation.The results showed that there was an increase in learning outcomes of the giring-giring dance material from Kalimantan in grade VIII C SMP Negeri 1 Cibadak. The improvement in the quality of the results can be seen from the increase in the score and mean score at the time of the action. In the first cycle the average value was 163, and in the second cycle it increased to 186.7. Meanwhile, the increase in activity can be seen from the observation in cycle I 31% and cycle II 38%.